Catarrhal Gingivitis Testing Algorithms in Children with Disabilities (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Despite certain achievements in the diagnosis of chronic catarrhal gingivitis in children with disabilities, as well as in improving the indicators of dental examination, treatment and prevention, the high level of this pathology, the trend of increasing morbidity is becoming one of the urgent problems. The frequency of chronic catarrhal gingivitis is due to its prevalence (80-98%), while the variety of clinical manifestations complicates diagnosis, treatment and prevention.